Islamic - "Stefon, Matt.(ed.)" (London, 2010)
Discusses various aspects of Islam, covering topics such as the importance of the Prophet in the Muslim community, the Qur'an, the Five Pillars, holy days, attitudes toward life and death, law, the various branches of Islam, and other related topics.
Keywords: Islam-Customs and practies